Evaluation of total antioxidant capacity of saliva and serum in caries-free and caries-active adults: An in-vivo study - Mithra N Hegde; Nidarsh D Hegde; Aparna Ashok; Shilpa Shetty (Wolters Kluwer Medknow Publications, 2013)
Context: Oxidative stress is defined as an imbalance between the production of reactive oxygen species and antioxidant defense systems which are widely recognized as an important feature of many diseases including dental caries, suggesting that total antioxidant status may be of importance in determining the progression of caries. Aim: The aim of this study was to estimate the total antioxidant capacity (TAC) in saliva and serum of caries-free and caries-active adults and to correlate the TAC level with DMFT index (D = decayed, M = missing, F = filled, T = teeth). Settings and Design: The present study included 100 healthy adults who were divided into four groups: Control, group I, group II, and group III, with a DMFT index 0, <3, <10, and >10, respectively. Materials and Methods: Saliva and serum samples were collected from all the four groups. The TAC of saliva and serum was estimated by phosphomolybdenum method. Statistical Analysis Used: One-way analysis of variance (ANOVA) was used to compare the TAC of saliva and serum. Only differences with "P" < 0.05 were considered statistically significant. Results: The mean TAC level of both saliva and serum increased significantly (P < 0.001) with the DMFT index. Conclusion: Total antioxidant capacity of saliva has a linear relation with caries, i.e., as the severity of caries increases, the TAC level also increases.